Concurrent Down-Regulation of PTEN and NKX3.1 Expression in Iranian Patients with Prostate Cancer - Nodouzi, Vahideh (Int Braz J Urol, 2015)
NKX3.1 and PTEN genes are involved in the development and progression of prostate cancer (PCa). Here, in line with other studies that correlated the expression of these two genes, we aimed at evaluating the expression pattern of these genes in clinical PCa samples. Collectively, 81 tissue samples including 45 human PCa and 36 benign prostatic hyperplasia (BPH) specimens were included in the study. The tissue samples were subjected to RNA extraction and subsequently to cDNA synthesis according to the kit manufacturer's protocol. Quantitative Real-Time PCR assay was performed for each sample in triplicate reactions. REST and SPSS software were used to statistically analyze PTEN and NKX3.1 gene expression data. Expression level of both NKX3.1 and PTEN genes was down-regulated in PCa samples compared to BPH samples. The relative expression ratio of PTEN and NKX3.1 was decreased to 0.155 and 0.003, respectively (P=0.000). The results of Chi-Square analysis revealed a significant correlation between the expression of these genes in both BPH and cancer groups (P=0.004 and 0.001, respectively). According to previous studies and our data, we concluded that the association between the down-regulation of PTEN and NKX3.1 genes contributed to the prostate tumorigenesis. This might highlight the interaction between the proteins encoded by these genes. Furthermore, this finding might be exploited for the development of innovative diagnostic and therapeutic approaches in PCa.